FAKTOR YANG MEMPENGARUHI PENGADOPSIAN MOBILE BANKING MENGGUNAKAN PENDEKATAN TAM - Rachmawati, Patricia; Lukman, Hendro (Jurnal Paradigma Akuntansi, 2025)
This study aims to determine the factors that influence the adoption of mobile banking. The subjects in this study were individuals who were 20 years old and had used mobile banking. Data was obtained by distributing questionnaires on social media in the form of a Google form. In this study, the data used is from 107 valid respondents. Data processing is done with SmartPLS 3.0 software. The results of this study indicate that perceived ease of use has no significant effect on attitude, perceived usefulness has a significant effect on attitude, attitude has a significant effect on adoption, perceived ease of use has no significant effect on adoption mediated by attitude, and perceived usefulness has a significant effect on significant to adoption mediated by attitude. The implication of this research is the need for banks to increase the convenience and benefits of using mobile banking so that customers feel that using mobile banking is easy and useful.